Adaptasi Skala Parent Child Relationship (IPPA) Versi Indonesia - Safaria, Triantoro; Rahayu, Yusti Probowati Rahayu; Rahaju, Soejantini (Jurnal Online Psikogenesis, 2024)
The parent-child relationship is a quality of interaction formed through the relationship between children and their parents, measured by the quality of communication, trust, and anger and alienation. Currently, there is a limited availability of scales to measure the parent-child relationship in the Indonesian context. Therefore, this study aims to adapt the Inventory of Parent and Peer Attachment (IPPA) scale by Armsden and Greenberg (1987) into the Indonesian language. The adaptation process followed the guidelines of the International Test Commission (ITC) for translating measurement tools from English to Indonesian. The research involved a sample of 333 junior high school students from two schools in Yogyakarta. Results from the Confirmatory Factor Analysis (CFA) for the father-child relationship scale showed that 23 items tested had standardized loading factors (SLF) ranging from 0.02 to 0.80. Based on SLF values below 0.50, 10 items were removed. The goodness-of-fit indicators for the father-child relationship scale showed a good model fit (RMSEA = 0.059, CFI = 0.982, TLI = 0.975). Similarly, results from the CFA for the mother-child relationship scale showed that 21 items tested had SLFs ranging from 0.05 to 0.84. Eight items were removed due to SLF values below 0.50. The goodness-of-fit indicators for the mother-child relationship scale showed an excellent model fit. It can be concluded that the adaptation of the IPPA scale has produced satisfactory results and can be used in the Indonesian context.